ИЗУЧЕНИЕ ФЕРМЕНТАТИВНОЙ АКТИВНОСТИ НЕФТЕЗАГРЯЗНЕННОЙ ПОЧВЫ ПРИ ВНЕСЕНИИ СВОБОДНЫХ И ИММОБИЛИЗОВАННЫХ КЛЕТОК МИКРООРГАНИЗМОВ РОДА RHODOCOCCUS - Чукпарова, А. У. (Eurasian Journal of Ecology, 2016)
The studies of the change of enzymatic activity of oil mudded soil before and after inoculation of free and immobilized cells of expanded clay and zeolite hydrocarbon micro-organisms were studied. It was established that the introduction of immobilized microbial cells increases the number of hydrocarbon-oxidizing microorganisms and increase the activity of catalases, urea’s and dehydrogenises